2011
DOI: 10.1371/journal.pone.0022116
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Pattern in Transmitochondrial Cytoplasmic Hybrid Cells Harboring Type 2 Diabetes-Associated Mitochondrial DNA Haplogroups

Abstract: Decreased mitochondrial function plays a pivotal role in the pathogenesis of type 2 diabetes mellitus (T2DM). Recently, it was reported that mitochondrial DNA (mtDNA) haplogroups confer genetic susceptibility to T2DM in Koreans and Japanese. Particularly, mtDNA haplogroup N9a is associated with a decreased risk of T2DM, whereas haplogroups D5 and F are associated with an increased risk. To examine functional consequences of these haplogroups without being confounded by the heterogeneous nuclear genomic backgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 31 publications
4
45
0
1
Order By: Relevance
“…MtDNA genetic variation can alter the expression of nuclear genes [19]. Cybrids are cell lines that share the nuclear genetic background and culture conditions and only differ in the mtDNA genotype.…”
Section: Discussionmentioning
confidence: 99%
“…MtDNA genetic variation can alter the expression of nuclear genes [19]. Cybrids are cell lines that share the nuclear genetic background and culture conditions and only differ in the mtDNA genotype.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, functional studies could contribute to better understanding of PARK2 , TFAM and mtDNA variation interplay and their involvement in PD pathogenesis. Recent findings in cybrid models demonstrated that mitochondrial haplogroups influenced mtDNA replication and transcription, and mitochondrial and nuclear genes expression pattern, involved in oxidative phosphorylation pathway [29,30]. Mitochondrial parameters were also changed in fibroblasts and leukocytes derived from EOPD patients carrying PARK2 mutations [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Whether haplogroups M and N are protective or risk-associated depends on the condition [2]. In fact, both mitonuclear interactions (retrograde signaling) and mitochondrial OxPhos function contribute to the development of disease [15, 18, 34], while variations in mitonuclear interactions have been reported in the two mtDNA haplogroups [15, 53]. Our data showed that the ratio of NAD + /NADH, a redox and energy stress marker, differed significantly between haplogroups M and N (Figure 9(b)), supporting the notion that haplogroups M and N exhibit distinct mitonuclear interaction patterns.…”
Section: Discussionmentioning
confidence: 99%